Comparison of markers of skin inflammation after injections of polylactic acid and threads based on polylactic acid - Larkina, S. A.; Makarenko, O. A.; Seletskaya, A. V. (Journal of Education, Health and Sport, 2020)
Aging processes lead to the tremendous changes in every tissues of human and skin is not an exception. Externally observable aging changes of the skin are caused by involutionary processes, which are happening on all levels, from skin to bones. The development of methods of prevention and treatment, which are aimed at fighting age-related changes in the skin and activating regenerative processes, is a live issue and has great scientific and practical significance. One of the important factors of skin aging is involutional changes occurring in the dermis. Currently, injections, based on polylactic acid are actively used as collagen stimulants in aesthetic medicine. Polylactic acid is a hydrophobic, biodegradable polymer derived from lactic acid. However, the mechanism of effect of polylactic acid on the components of the dermis, as well as the morphohistochemical status of the implant itself and the effect on markers of skin inflammation remains insufficiently understood and are actively discussed in the literature. We carried out biochemical studies of rat skin in order to study the effect of polylactic acid on markers of skin inflammation. To assess the condition of the skin of rats, after the administration of the studied drugs, the following was determined: • marker of inflammation - the activity of neutrophilic elastase; • factor of the state of cell membranes - the activity of lysosomal acid phosphatase; • the state of nonspecific antimicrobial protection - the activity of lysozyme. The conducted study allows us to conclude about the relative safety of preparations based on polylactic acid, the subdermal administration of which after 60 days shows minor signs of inflammation and practically does not affect the nonspecific antimicrobial protection of the skin of laboratory rats.